Performance Analysis of Scheduling Schemes for Femto to Macro Interference Coordination in LTE-Femtocell Deployment Scenario - Ainul, Rafina Destiarti; Mahmudah, Haniah; Wijayanti, Ari (EMITTER International Journal of Engineering Technology, 2016)
Deploying femtocells that have low power level in LTE with small coverage area is an alternative solution for mobile operators to improve indoors network coverage area as well as system capacity. However deploying femtocells (HeNB) that were used co-channel frequency, can be brought about interference problem to the Macro BTS (eNB). Close Subscriber Group (CSG) of HeNB allows only User equipment (UE) to access HeNB. HeNB is the source of interference for UE who cannot access it. Therefore it is necessary for interference coordination methods among the HeNB and eNB. The methods are ICIC (Intercell Interference Coordination) and eICIC (enhanced Intercell Interference Coordination). Â This paper proposed performance analysis of scheduling schemes for Femto to macro interference coordination that allocated resource in the frequency and time domain using LTE-Femtocell suburban and urban deployment scenario. Simulation result using ICIC methods can improve SINR performance 15.77 % in urban and 28.66 % in suburban, throughput performance 10.11 % in urban and 21.05 % in suburban. eICIC methods can improve SINR performance 17.44 % in urban and 31.14 % in suburban, throughput performance 19.83% in urban and 44.39 % in suburban.The result prove using eICIC method in time domain resource have better performance than using ICIC method in frequency resource. However using eICIC method in suburban deployment scenariocan increase the performance of SINR and throughput more effective than using eICIC method in urban deployment scenario.